It is all about an appealing environment: Linking the learning environment dimensions with student engagement in Ethiopian higher education context - Bekalu Tadesse Moges; Yalalem Assefa; Shouket Ahmad Tilwani; Yibeltal Aemro Azmera (Social Sciences and Humanities Open)
Student engagement and the learning environment have gained momentum within the educational research space as valid factors in determining the quality of education. However, empirical evidence on the relationships between the learning environment and student engagement remains scant in the context of higher education in Ethiopia. This article examined the association between student perception of the learning environment and student engagement (affective, agentic, behavioural, and cognitive engagement). The study employed a quantitative research approach, specifically a correlational design. 334 undergraduate students selected via stratified random sampling participated in the study. Whether and how engagement is related to the learning environment within higher education institutions is examined using structural equation modelling. Results indicated that the learning environment is significantly related to cognitive, affective, behavioural, and agentic engagements. Moreover, two-group structural analysis revealed that the relationship between learning environment and cognitive engagement is significantly different for males and females, whereas other engagement dimensions did not exhibit such differences. Student engagement and the learning environment showed a low coefficient of correlation. The results of this study will contribute to designing learning environment variables in higher education that are gender-friendly and optimize engagement. Based on the results, implications are drawn for the context of higher education in Ethiopia.